CLASSROOM DISCUSSION: AN ACTIVITY TO PROMOTE SPEAKING IN A FOREIGN LANGUAGE - Lidya, Marina; Amir, Melvina (TELL - US JOURNAL, 2016)
In the era of information and technology, every people are demanding to master the English language for communication purpose. Nowadays English is widely used for different purpose such as academic, business, diplomacy, news and information, entertainment and others. It proves that the English language has become a basic requirement for students and job seeker in this increasingly globalized world. In order to meet the needs for international communication, Indonesians students need to be proficient in English, especially in oral communication skill. Communication skill is highly needed by students in order to prepare them for their possible further academic career and future workplace. This paper is intended to discuss about classroom discussion. Classroom discussion is one kinds of activity that is done by the teacher in teaching and learning. In this activity, the students will present their opinions to the class. Therefore, the students get the opportunities to speak English well. It also gives valuable experience for them to prepare themselves to use English in multi society where English is a demanding tool for communication in our today’s life.